Decolorization of organic dyes by gold nanoflowers prepared on reduced graphene oxide by tea polyphenols. Issue 9 (9th December 2015) - Šimšíková, M.; Bartoš, M.; Čechal, J.; Šikola, T.
Abstract : The green approaches for chemical syntheses are becoming important in various fields comprising chemical synthesis. Abstract : Green approaches for chemical syntheses are becoming important in various fields. Here, we report on the formation of 3D branched gold nanoparticles (nanoflowers) on graphene oxide surface (rGO-AuNFs) in the presence of green tea without requiring any additional seeds or surfactants. The morphology, composition, and optical properties of the composite have been characterized by scanning electron microscopy (SEM), Raman spectroscopy, Fourier transformation (FT-IR) infrared spectroscopy, X-ray photoelectron spectroscopy, UV-Vis spectroscopy, and fluorescence spectroscopy. We demonstrate the catalytic efficiency of rGO-AuNFs by measurement of the degradation of three commercial organic dyes – Safranin T, Eosin Y, and Congo red. The observations indicate the enhanced reduction of the mentioned dyes in comparison with uncatalyzed measurements. Contrary to common approaches, no irradiation is required for dye decolorization in the presence of NaBH4 . This makes the presented procedure attractive for application in catalyst materials.